A Peculiar Cause of Shock: Analysing Two Clinical Cases - João Oliveira; Alberto Costa-Silva; Luís Vale; Daniel Costa; Rui Almeida-Pinto; Carlos Martins-Silva; Tiago Antunes-Lopes; João Silva (Case Reports in Urology)
Introduction. Pheochromocytoma is a rare neoplasia arising from the adrenal medulla that secretes catecholamines. Those afflicted by this condition can present a wide range of symptoms. One of the most common is paroxysmic hypertension. Interestingly, although rare, some patients present with shock. We describe two cases of pheochromocytoma in which the initial presentation was shock. Case 1. 49 year-old woman, with a history of resistant hypertension, presented to the emergency department with thoracic pain and fever. EKG, echocardiogram (ECC), and myocardial necrosis markers were compatible with Takotsubo syndrome (TS). CT demonstrated a staghorn calculus, hydronephrosis, and signs compatible with xanthogranulomatous pyelonephritis in the right kidney. Additionally, and incidentally, it revealed a 60 mm nodule on the right adrenal gland. Piperacillin/tazobactam was started immediately, and the patient was submitted to urgent upper urinary tract drainage. This procedure was complicated by a cardiorespiratory arrest that was treated with adrenaline administration. The patient was admitted to the ICU due to multifactorial shock and started alpha and, posteriorly, beta blockage. Biochemical adrenal incidentaloma endocrinologic study was negative (under hemodialysis). Multiorgan failure progressively improved. After 2 weeks, the patient was submitted to a laparoscopic transperitoneal right adrenalectomy. No complications were reported. Histological analysis revealed a pheochromocytoma. Case 2. 28-year-old woman presented to the emergency department with headaches and nausea. Vitals were compatible with shock. CT revealed an incidental 72 mm mass on the right adrenal. EKG, ECC, and myocardial necrosis markers were compatible with TS. The patient was started on alpha and, posteriorly, beta blockage. Adrenal incidentaloma endocrinological study demonstrated high urinary catecholamines. Right transperitoneal adrenalectomy was performed. No complications were noted. Histological analysis revealed a pheochromocytoma. Conclusion. Pheochromocytoma can present with complex, enigmatic, and rare clinical pictures. Clinicians should be wary of the possibility of this diagnosis when managing adrenal masses.